Emerging topics in dementia care and services. Issue 7 (10th July 2021) - Wolff, Jennifer L.; Benge, Jared F.; Cassel, Christine K.; Monin, Joan K.; Reuben, David B.
Abstract: Background: The National Institute on Aging (NIA), in conjunction with the Department of Health and Human Services as part of the National Alzheimer's Project Act (NAPA), convened a 2020 Dementia Care, Caregiving, and Services Research Summit Virtual Meeting Series . This review article summarizes three areas of emerging science that are likely to grow in importance given advances in measurement, technologies, and diagnostic tests that were presented at the Summit. Results: Dr. Cassel discussed novel ethical considerations that have resulted from scientific advances that have enabled early diagnosis of pre‐clinical dementia. Dr. Monin then summarized issues regarding emotional experiences in persons with dementia and their caregivers and care partners, including the protective impact of positive emotion and heterogeneity of differences in emotion by dementia type and individual characteristics that affect emotional processes with disease progression. Finally, Dr. Jared Benge provided an overview of the role of technologies in buffering the impact of cognitive change on real‐world functioning and their utility in safety and monitoring of function and treatment adherence, facilitating communication and transportation, and increasing access to specialists in underserved or remote areas. Conclusions: National policy initiatives, supported by strong advocacy and increased federal investments, have accelerated the pace of scientific inquiry and innovation related to dementia care and services but have raised some new concerns regarding ethics, disparities, and attending to individual needs, capabilities, and preferences.